The role of nanomaterials and nanostructured surfaces for improvement of biomaterial peculiarities in vascular surgery: a review. (17th November 2021) - Fodor, Marius; Fodor, Lucian; Bota, Olimpiu
Abstract: Nanoparticles are defined as objects, which have one, two or three external dimensions in the nanoscale, ranging from 1 to 100 nm (ISO/TR 18401:2017). In order to reduce vascular complications like thrombosis, infection and graft rejection, nanoparticle technologies show growing applications in the field of angiology and vascular surgery. The aim of this review is to evaluate the literature concerning the role of nanoparticles as a carrier for vascular agents and for improving biomaterial particularities used as substitutes in vascular surgery. While important advances have been achieved in vascular medicine with the emerging of nanotechnologies, much more fundamental and clinical work needs to be done before vascular implants and therapies reach the ideal state.